Bagasse ash ceramic glaze - Rugthaicharoencheep, Sansanee; Bangluang, Vararee; Panthong, Emwagee; T.saengchantara, Wanna (Bulletin of Applied Sciences, 2016)
Sugar industry produces bagasse ash waste many tons per year. The only ash utilization so far is for soil improvement for sugar cane plantation. The utilization of bagasse ash from sugar manufacture to produce ceramic glaze is studied. The glaze consists of 3 major raw materials: bagasse ash, clay, and feldspar. Chemical analysis by X-ray fluorescence (XRF) indicates that bagasse ash contains 71% SiO2, 9% Al2O3 , and 8% CaO as major composition. Phase analysis by X-ray diffraction (XRD) shows quartz as dominant phase. Glaze formulae for 1250 °C firing temperature are determined using tri-axial blend method. In this study the appropriate amount of bagasse ash for grazing on decorative ware is between 35-65%, clay 15-50% and feldspar 10-70%. The addition of 10% Caco3 helps in reducing the firing temperature. The glaze colors vary from yellow to dark brown depends on the amount of added ash. If high amount of ash is added, the glaze color becomes dark brown. The bagasse ash glaze can be used on decorative ware but is not suitable for tableware because it does not pass the crazing resistance test using an autoclave.